2016
DOI: 10.1016/j.ajhg.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TBCK, Encoding TBC1-Domain-Containing Kinase, Lead to a Recognizable Syndrome of Intellectual Disability and Hypotonia

Abstract: Through an international multi-center collaboration, 13 individuals from nine unrelated families and affected by likely pathogenic biallelic variants in TBC1-domain-containing kinase (TBCK) were identified through whole-exome sequencing. All affected individuals were found to share a core phenotype of intellectual disability and hypotonia, and many had seizures and showed brain atrophy and white-matter changes on neuroimaging. Minor non-specific facial dysmorphism was also noted in some individuals, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(110 citation statements)
references
References 13 publications
(15 reference statements)
10
80
1
9
Order By: Relevance
“…In 1 additional family, we identified a novel disease-gene relationship, a new disease associated with a known gene, KIF1A, 14 and in 2 other families we identified the novel IPN genes, TBCK and MCM3AP. 13,19 Our diagnostic rate (24%) is within the 11% to 53% range of recently reported IPN cohorts ( Table 2) [4][5][6][7][8][9][10] ; and similar to the percentage of the total number of diagnoses in known genes in these IPN cohorts (29%; 102/354) ( Table 2). The wide range in diagnostic rates for these cohorts may be due to the use of different variant pathogenicity criteria and/or the number of genetic tests performed prior to WES; both make studies difficult to compare.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In 1 additional family, we identified a novel disease-gene relationship, a new disease associated with a known gene, KIF1A, 14 and in 2 other families we identified the novel IPN genes, TBCK and MCM3AP. 13,19 Our diagnostic rate (24%) is within the 11% to 53% range of recently reported IPN cohorts ( Table 2) [4][5][6][7][8][9][10] ; and similar to the percentage of the total number of diagnoses in known genes in these IPN cohorts (29%; 102/354) ( Table 2). The wide range in diagnostic rates for these cohorts may be due to the use of different variant pathogenicity criteria and/or the number of genetic tests performed prior to WES; both make studies difficult to compare.…”
Section: Discussionsupporting
confidence: 83%
“…For example, interrogation of the WES data-set in this study resulted in 3 discoveries within our cohort; a novel disease associated with the gene KIF1A, 14 and 2 novel diseasecausing genes, TBCK and MCM3AP. 13,19 In all 3 of these cases, additional evidence, including identification of additional patients and functional studies, was necessary to support pathogenicity of the variants. Had we not conducted additional research in these 3 cases, one could presume that the genes would still have been published as cohorts and these families would have received diagnoses following Similarly, the identification of MORC2 in family #23 reported here was the result of a reanalysis of WES data that was several years old (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated these genes and saw that the significant signal of these 11 genes was from CC data. C5orf42, HSD17B4, PMPCA, SAMD9L, SCYL1 and TBCK were also reported in NDD studies [36][37][38][39][40][41] . The Epi K. consortium and Epilepsy Phenome/Genome Project 13 used the same CC data set as our current study and reported 7 significant autosomal genes (DEPDC5, GABRG2, GRIN2A, KCNQ2, LGI1, PCDH19, SCN1A); all seven had gTADA PPmax > 0.9, and 6/7 (except GRIN2A) had PPmax > 0.95.…”
Section: Resultsmentioning
confidence: 59%
“…Mutations in TBCK cause a neurodevelopmental syndrome with intellectual disability, coarse face, congenital hypotonia, leukoencephalopathy, progressive motor neuronopathy, and seizures (Bhoj et al, 2016;Chong et al, 2016;Ortiz-González et al, 2018). As suggested by bioinformatic analysis, TBCK encodes a putative Rab GTPase-activating protein, although its function remains elusive.…”
Section: Autophagy and Neurodevelopmental Disorder With Epilepsymentioning
confidence: 99%
“…As suggested by bioinformatic analysis, TBCK encodes a putative Rab GTPase-activating protein, although its function remains elusive. Loss-of-function mutations in TBCK lead to inhibition of mTORC1 and, thus, to uncontrolled autophagy induction in patient-derived fibroblasts (Bhoj et al, 2016;Ortiz-González et al, 2018). In this model, loss of TBCK results in increased number of APs accompanied by an augmented autophagic flux insensitive to pro-autophagic stimuli (Ortiz-González et al, 2018).…”
Section: Autophagy and Neurodevelopmental Disorder With Epilepsymentioning
confidence: 99%